A new record of Bulbophyllum section Aeschynanthoides from Vietnam - Truong, Voung Ba; Vermeulen, Jaap J.; Truong, Tam Quang (Lankesteriana: International Journal on Orchidology, 2019)
Bulbophyllum hainanense is an addition to the Flora of Vietnam. Previously, Vietnamese material of this species was listed as Bulbophyllum hymenanthum, a similar-looking species. This paper provides a description and illustration of the Vietnamese material of B. hainanense.